(untitled) (PANGEEA, 2025)
Diamond, from mineral to gemstone. Diamond is considered the most important gemstone used in jewelry. As known from prehistoric times, diamonds were used both as jewelry and as a means of hoarding, accompanying human history over the centuries. Sometimes, diamonds have caused the onset of significant historical events. The paper will describe the properties of this mineral and an overview of the history of the most famous diamonds in the world.